Bouveret syndrome: A challenging case of impacted gallstone within the fourth part of the duodenum. (May 2022) - Smith, Emma; Zhao, Sarah; El Boghdady, Michael; Sabato-Ceraldi, Serena
Abstract: Introduction and importance: Bouveret syndrome is a rare condition characterised by gastric outlet obstruction secondary to a gallstone fistulating into the proximal duodenum or pylorus. Although rare, this condition carries a high mortality rate and no current standardised guidelines for management. Case presentation: We present a case of a patient in their 60s with recurrent small bowel obstruction secondary to a cholecysto-duodenal fistula and large gallstone which became impacted in the fourth part of the duodenum. The patient had a P-POSSUM Score of 14% mortality and 60% morbidity risk, had multiple co-morbidities, was bedbound, BMI 59 and had been deemed high risk for general anaesthetic at oncology centre for a 10 × 10 cm likely gynaecological malignancy a month prior to this admission. Clinical discussion: In contrast to existing literature, endoscopic lithotripsy was considered but not attempted due to unavailability of this service locally. Surgical intervention was decided based on radiological features of impending duodenal perforation on CT imaging and multiple disciplinary team discussion. The patient was managed with open enterolithotomy at the duodeno-jejunal (DJ) flexure and discharged 3 weeks post-operatively at her pre-operative baseline. Conclusion: This is the first report to our knowledge to describe successful surgical management of a gallstone impacted in the fourth part of the duodenum. In cases where anatomical location of impaction precludes retrieval via simple gastrostomy, we suggest using high pressure flush to mobilise the stone to more favourable location distally. We emphasise that stone size should be considered when planning surgical management. Highlights: Consider Bouveret syndrome as a differential in patients with small bowel obstruction, and pneumobilia even without history of gallstones. Imaging often underestimates the full size of ectopic gallstones and thus risk of impaction may not be fully evaluated. Management requires multidisciplinary team involvement between radiology, surgical, endoscopist and anaesthetic specialties. Enterolithotomy can be considered for large, impacted stones and can be a safe option in patients with multiple morbidities. We suggest techniques using high pressure flush to mobilise inaccessible stones to a more favourable distal location.